Techno-economic appraisal of alternative distribution network design options - Gan, Chin Kim; Low , Siew Yi (2012)
This paper presents the methodology and distribution network model used for the assessment of alternative distribution network design strategies in terms of the cost and benefits involved. In contrast to network specific design approach, a statistical distribution network design model has been adopted in this work. The investigation into the viability of three voltage levels design (132/11/0.4kV) when compared to conventional four voltage levels design (132/33/11/0.4kV) for a typical rural case have been carried out. The technical impact and economic implications of both design options have been quantitatively evaluated and quantified.